Il disagio in adolescenza: tra insuccesso scolastico e disincanto. Prospettive di inclusione nella scuola secondaria di secondo grado - Sabina Falconi (Firenze University Press, 2012)
Early in adolescence, biological changes in brain structure and connectivity within the brain interact with increased experience, knowledge, and changing social demands to produce rapid cognitive growth. The cognitive developments result in greater self-awareness, greater awareness of others and their thoughts and judgments, the ability to think about abstract, future possibilities, and the ability to consider multiple possibilities at once. The text shows why adolescence is a time of "thinking in a new key", and how young people need the secondary school to resulting problems range from common alienation to self-destructive behavior.